[PP.34.33]: HIGH SENSITIVE C-REACTIVE PROTEIN AND BLOOD PRESSURE IN ISCHEMIC STROKE. (June 2015) - Brescacin>, L.>; Alonzo, C.; Zurru, M.C.; Luzzi, A.; Guido, B.; Camera, L.; Cristiano, E.; Waisman, G.
Abstract : Objective: Systemic inflammation may influence blood pressure (BP) control by means of endothelial dysfunction and alteration of the renin-angiotensin system. As a result, hypertension may be in part an inflammatory disorder; however, clinical data linking inflammation with BP control are scarce. We aim to evaluate the relationship between an inflammatory marker (hs-CRP), acute-phase and one-month BP, and early outcomes in an ischemic stroke cohort. Design and method: Acute ischemic stroke patients were prospectively included in PROTEGE-ACV, a multidisciplinary secondary stroke prevention program. Demographic data and vascular risk factor profile and control were prospectively evaluated in the acute-phase and one month after stroke; 30-day hs-CRP (cut-off value of 3 mg/L), cognitive function (clock-drawing test –CDT– and MMSE, disability (Barthel index and m-Rankin scale), recurrence and mortality were evaluated. Patients with transit ischemic attack, unusual mechanisms of stroke (TOAST 4) and those with incomplete data were excluded from the analysis. A univariate analysis and a logistic regression model were performed. Results: 695 patients (mean age 75 ± 10 years, 51% female) were included between December 2006 and December 2013. In patients with hs-CRP >3 mg/L (n 431), prevalence of hypertension, atrial fibrillation, obesity, metabolic syndrome and peripheral vascular disease was higher; cardioembolic stroke was more frequent and antihypertensive drugs more prescribed. They also had higher SBP, DBP and PP in the acute-phase and one-month after stroke (table). Patients with hs-CRP >3 had worse outcomes: m-Rankin 0-1 (67% vs 75%; p 0.05); Barthel index (90 ± 11 vs 94 ± 12; p 0.01) and cognitive impairment by MMSE (21% vs 12%; p 0.01). Predictors of elevated hs-CRP were acute-phase SBP (OR 1.6; CI95% 1.28–2.1; p 0.001) and one-month SBP (OR 1.6; CI95% 1.18–1.81; p 0.001) and DBP (OR 1.13; CI95% 1.08–1.30; p 0.01) Figure. No caption available. Conclusions: There is a significant relationship between inflammation and higher BP levels during the acute-phase and one month after an ischemic stroke; patients with higher hs-CRP also had worse outcomes. These findings suggest that inflammation and endothelial dysfunction could be the link between hypertension and post stroke disability.